Determining the Impact of Software Engineering Research on Practice. - Osterweil, Leon J.; Ghezzi, Carlo; Kramer, Jeff; Wolf, Alexander L. (Computer (00189162), 2008)
The article discusses the Impact Project, which provides a scholarly assessment of the impact software engineering research has had on software engineering practice. The assessment is manifested in a series of studies and briefings, which involves literature searches and personal interviews. According to the article, among the efforts that typify the extent and nature of software engineering research's impact on software engineering practice is configuration management. The objectives of the Impact Project are also discussed.